The Relationship Between a History of Hypertension, Diabetes Mellitus, and Gout with the Incidence of Coronary Heart Disease at Lavalatte Hospital - Siti Nur Ayati Ningsih; Bayu Budi Laksono; Alfunnafi' Fahrul Rizzal (Akademi Keperawatan Yarsi Samarinda, 2026)
Coronary heart disease is a disorder of heart function caused by a lack of blood supply to the heart muscle due to blockage or narrowing of the coronary arteries resulting from damage to the artery walls. Damage to the lining of the coronary arteries is caused by blockages or narrowing of the coronary arteries (blood vessels in the heart that supply food and oxygen to heart cells) due to fatty deposits that accumulate on the artery walls (plaque). According to data from the Malang City Health Office, there were 730 new cases of coronary heart disease in Malang City in the 2014–2015 period. Although specific data for 2019 appears to be less publicly available, this figure provides an indication that CHD has been a significant health burden in Malang City during that period. Based on a preliminary study conducted by researchers on October 10, 2025, using interviews in the Platinum 4 room at Lavalette Hospital, which is a cardiovascular room, data was obtained on patients with CHD who had no history of hypertension, no diabetes, but had a history of gout since 2019 and had experienced two recurrences in the past year. The purpose of this study was to determine how medical history affects the risk of CHD at Lavalette Hospital. This study used a case-control design with data collected directly through structured interviews and measurements of blood pressure, uric acid, and blood sugar. The results of this study show that the majority of respondents at Lavalette Hospital have a history of disease (hypertension, diabetes mellitus, uric acid) in the high category (84.6%), with the highest prevalence in the elderly age group, while coronary heart disease (CHD) in respondents is dominated by the highrisk category (82.1%)12. The conclusion is that there is a statistically significant relationship between medical history and the incidence of CHD at Lavalette Hospital (P = 0.025), with a weak positive correlation (r_s = 0.358)13.